2011
DOI: 10.1002/jemt.21033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low‐level laser associated with osteogenic proteins recombinant human BMP‐2 and Hevea brasiliensis on bone repair in Wistar rats

Abstract: This study analyzed the newly formed bone tissue after application of recombinant human BMP-2 (rhBMP-2) and P-1 (extracted from Hevea brasiliensis) proteins, 2 weeks after the creation of a critical bone defect in male Wistar rats treated or not with a low-intensity laser (GaAlAs 780 nm, 60 mW of power, and energy density dose of 30 J/cm(2)). The animals were divided into two major groups: (1) bone defect plus low-intensity laser treatment and (2) bone defect without laser irradiation. The following subgroups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The results showed that P-1 increased the deposition of collagen fibers, whereas rhBMP-2 significantly increased bone neoformation at the defect site. The latter was considered to be more effective in the process of bone consolidation (Iyomasa et al, 2012). In the present study, the new fibrin sealant was used as a scaffold for cell adhesion and proliferation and was also found to be a good carrier of bone proteins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that P-1 increased the deposition of collagen fibers, whereas rhBMP-2 significantly increased bone neoformation at the defect site. The latter was considered to be more effective in the process of bone consolidation (Iyomasa et al, 2012). In the present study, the new fibrin sealant was used as a scaffold for cell adhesion and proliferation and was also found to be a good carrier of bone proteins.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, the fibrin sealant was combined with two promising osteogenic factors, rhBMP-2 and protein P-1 extracted from the latex of the rubber tree H. brasiliensis, in order to determine the osteoconductive potential of this combination in bone healing. The osteoinductive potential of pure and recombinant BMP-2 and its applicability to the healing of bone defects have been reported (Iyomasa et al, 2012). In parallel to BMPs, other natural substances have been explored in studies on bone regeneration, including fraction P-1 extracted from the rubber tree which exerts osteoconductive activity through the acceleration of bone neoformation, particularly in early stages of the healing process, as a result of its angiogenic properties and biocompatibility (Balabanian et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Springer et al [49] studied the application of BMP in the irradiated mandible and found that BMP could cooperate with bFGF and result in predictable bone generation. Other studies also identified that BMP could enhance the generation and repair of bones after radiotherapy [50,51]. …”
Section: Strategies For Improving the Survival Rate Of Implants In Irmentioning
confidence: 99%
“…There are many consolidated reports of the application of bone biomaterials of xenogeneic origin (Iyomasa et al, 2012), especially bovine, for oral rehabilitation (Bornstein et al, 2008; Kim et al, 2009; Pieri et al, 2008; Simunek et al, 2008) and orthopedic purposes (Chiang et al, 2008; Rosito et al, 2008; Schultheiss et al, 2005). This vast scientific literature about bovine grafting biomaterials even justifies its use as standard during experimentation with new synthetic materials (Kim and Kim, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although it may seem logical that other farm animals may also be used for the extractions of bone grafting biomaterial bases, this does not usually happen. Even though sheep may present several advantages over cattle (such as lower demand for space and shorter periods for reproduction, breeding, and slaughtering), such animals are used only as in vivo models in experimental bone grafting studies (Cheng et al, 2005; Collignon et al, 1997; Giavaresi et al, 2008; Iyomasa et al, 2012; Paknejad et al, 2008; Pereira et al, 2011; Santoni et al, 2008; Swennen et al, 2005; Vlaminck et al, 2008) or in vitro with ovine origin cells (Rhodes et al, 2004; Schmitt et al, 2008). Also, it has already been demonstrated that ovine bone has similar characteristics to human bone (Grimm et al, 2001).…”
Section: Introductionmentioning
confidence: 99%